2018
DOI: 10.1021/acsami.8b06616
|View full text |Cite
|
Sign up to set email alerts
|

Rear-Surface Passivation by Melaminium Iodide Additive for Stable and Hysteresis-less Perovskite Solar Cells

Abstract: Surface passivation of perovskite grains is one of the promising methods to reduce recombination and improve stability of perovskite solar cells (PSCs). We herein report the effect of a melaminium iodide additive on the photovoltaic performance of PSCs based on (FAPbI)(CsPbBr) perovskite. Cyclic -C═N- and primary amine in melamine are a good hydrogen bond acceptor and Lewis base, which can interact with both the organic cation and Lewis acidic lead iodide in the perovskite film. Melaminium iodide is synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 71 publications
1
58
0
Order By: Relevance
“…There are many reports analyzing the origin of hysteresis in PSCs such as charge trapping and de‐trapping as a result of crystal defects, band bending between the different interfaces and ionic motions within perovskite. Park et al have reported adding melamine hydroiodide can effectively decrease the hysteresis of perovskite devices as surface passivation of perovskite grains . In our opinion, MALA has three amine groups that may provide hydrogen bonding to [PbI 6 ] 4− .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…There are many reports analyzing the origin of hysteresis in PSCs such as charge trapping and de‐trapping as a result of crystal defects, band bending between the different interfaces and ionic motions within perovskite. Park et al have reported adding melamine hydroiodide can effectively decrease the hysteresis of perovskite devices as surface passivation of perovskite grains . In our opinion, MALA has three amine groups that may provide hydrogen bonding to [PbI 6 ] 4− .…”
Section: Resultsmentioning
confidence: 82%
“…Park et al have reported adding melamine hydroiodide can effectively decrease the hysteresis of perovskite devices as surface passivation of perovskite grains. [20] In our opinion, MALA has three amine groups that may provide hydrogen bonding to [PbI 6 ] 4À . As shown in Scheme 1 and Figure S1b, Supporting Information, we suppose that some MALA through bonding to [PbI 6 ] 4À to affect the crystal lattice of the MAPbI 3 perovskite and others functioned as MAPbI 3 grains surface passivation.…”
Section: Resultsmentioning
confidence: 97%
“…Absorbance spectra and Tauc‐plots in Figure S8, Supporting Information, display little change in the absorption edges before and after NMAI treatment, which is consistent with results from XRD measurement. [ 45 ] Given the fact that typical 2D/3D stacked perovskite film configuration usually induces absorbance edge change, [ 21,23,46 ] we can infer that the quantity of formed low‐dimensional perovskite after NMAI treatment is indeed so negligible that it cannot affect the bandgap.…”
Section: Resultsmentioning
confidence: 99%
“…This process deprotonated the imidazolium cations and released the imidazole, where cation exchange improved film quality. Kim et al reported a hysteresis‐free PSC with melaminium iodide additive, and the hysteresis index decreased from 0.1282 to 0.0674 (Figure g) …”
Section: Passivation Of Perovskite Layermentioning
confidence: 94%